Pengaruh active learning terhadap hasil belajar passing bawah bola voli pada siswa SMP - Kurnia, Daniela Putri; Yulfadinata, Afifan; Ridwan, Mochamad; Ningsih, Yuni Fitriyah; Prihanto, Junaidi Budi (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
The low learning outcomes of students at MTsN 2 Sidoarjo in the subject of underhand passing in volleyball, with only 6.67% of students achieving the minimum passing grade, demonstrate the importance of implementing more effective learning methods that can increase student engagement. The main objective of this study was to determine the effectiveness of the Active Learning Method in teaching underhand passing in volleyball. This study used a quasi-experimental design based on the Nonequivalent Control Group Design model. The study involved two classes selected using purposive sampling, one group with 32 students for the experimental group and the other with 32 students for the control group. The pre-test and post-test results in this study used the same instrument, namely the underhand passing skill test. In this study, the t-value was -0.252 and the p-value was 0.802, both of which were much higher than the level of 0.05. The pre-test scores did not show a significant difference, so both groups had equivalent initial abilities. The experimental group showed a statistically significant improvement after the procedure, producing a post-test score of 55.91, while the control group scored 31.91. The results of the paired sample t-test and independent sample t-test showed that the Active Learning Method significantly improved underhand passing skills. Based on these results, it was concluded that active learning is superior to conventional methods because it allows students to collaborate, receive feedback on their skills, and engage in hands-on practice. Further research should examine alternative learning methods related to sports and include additional factors, such as student engagement and participation, to achieve a more comprehensive understanding of the importance of active learning